Penyuluhan Potensi Skoliosis Untuk Mengatasi Perbaikan Postur Tubuh Pada Anak SD Negeri 1 Taruban - Muninggar Setia Pratama; Tasya Ghea Amanda; Heru Purnomo; Ilham Yugantara; Sintia Herlina; Taufik Eko Susilo; Arif Pristianto; Wahyuni Wahyuni (Jurnal Pengabdian Masyarakat, 2023)
Scoliosis occurs due to congenital, traumatic, degenerative or idiopathic. And the comparison that occurs in scoliosis is, women experience scoliosis by 5: 7 than men. To determine the risk factors associated with the potential occurrence of scoliosis and posture improvement in children of SD Negeri 1 Taruban, Surakarta, educational activities were carried out in the form of counseling packaged with presentation methods, simulation of media leaflets. Based on the assessment of Low Back Pain knowledge in community members conducted before the counseling took place, results were obtained in the form of 19 people less, 10 people Enough and 3 people in the good category. Based on the assessment of Ergonomics knowledge in the correct posture of community members carried out after the counseling process took place, results were obtained in the form of 22 people having knowledge in the good category, 8 people having knowledge in the sufficient category, 2 people having knowledge in the less category.